Pengaruh Pembelajaran Kewirausahaan (PKW) terhadap Minat Berwirausaha Siswa di SMK Pasuruan - Dea Ajeng Kirana; Sugeng Pradikto (Jurnal Kajian dan Penelitian Umum, 2025)
The aim of this research is to find out how entrepreneurship education influences the entrepreneurial interest of class XI students at SMK Muhammadiyah Pasuruan. The findings of this research can help SMK Muhammadiyah Pasuruan develop a PKW curriculum and provide advice to related parties on how to encourage students' interest in entrepreneurship. This research also tests the idea that students' interest in entrepreneurship will increase along with the frequency of entrepreneurship practicum. This research uses a quantitative approach using questionnaires and correlational or causal methodology. The sample used by researchers is the entire population, which is often known as a saturated sample (census sample). The collected data will then be tested for validity and reliability using statistical software such as SPSS. The high level of reliability of this study is demonstrated by its findings. Cronbach's Alpha values ​​for both variables were higher than the acceptance criterion of 0.7, indicating this. Data from this instrument can be relied on to accurately represent the variables being measured, because it has a high level of reliability. This research can be continued to the next stage of analysis.